Introduction : Downtown Southern Route (DSR) - Mironowicz, Izabela; Ryser, Judith (AESOP, 2010)
The City of Wrocław has been facing heavy traffic problems, especially in the inner city and on the inner city ring. Not only it is a problem of everyday commuting, but also for transit that uses the downtown street system. Therefore, the municipality planned to build a southern downtown ring that connects Plac Społeczny in the east to the new development area in the west. This road is believed to change the existing situation, to release the city centre from transit traffic, and to reduce congestion and pollution in the old town. The current proposal for the Downtown Southern Route (DSR) consists of a high-capacity six-eight lane ring road, which will be made up from existing and readapted streets, as well as completely new road connections. The proposed route is to run south of the Old Town, connecting Kazimierza Pułaskiego with Poznańska and thereby creating a high-capacity on the edge of the inner city. It is important to note that the proposed planning area is one of the most congested in the city where traffic flows at an average speed 20-30 km/h and are often interrupted.
Book of proceedings: Urban change : The prospect of transformation